Plant uptake and availability of antimony, lead, copper and zinc in oxic and reduced shooting range soil. (July 2018) - Hockmann, Kerstin; Tandy, Susan; Studer, Björn; Evangelou, Michael W.H.; Schulin, Rainer
Abstract: Shooting ranges polluted by antimony (Sb), lead (Pb), copper (Cu) and zinc (Zn) are used for animal grazing, thus pose a risk of contaminants entering the food chain. Many of these sites are subject to waterlogging of poorly drained soils. Using field lysimeter experiments, we compared Sb, Pb, Cu and Zn uptake by four common pasture plant species ( Lolium perenne, Trifolium repens, Plantago lanceolata and Rumex obtusifolius ) growing on a calcareous shooting range soil under waterlogged and drained conditions. To monitor seasonal trends, the same plants were collected at three times over the growing season. Additionally, variations in soil solution concentrations were monitored at three depths over the experiment. Under reducing conditions, soluble Sb concentrations dropped from ∼50 μg L −1 to ∼10 μg L −1, which was attributed to the reduction of Sb(V) to Sb(III) and the higher retention of the trivalent species by the soil matrix. Shoot Sb concentrations differed by a factor of 60 between plant species, but remained at levels <0.3 μg g −1 . Despite the difference in soil solution concentrations between treatments, total Sb accumulation in shoots for plants collected on the waterlogged soil did not change, suggesting that Sb(III) was much more available for plant uptake than Sb(V), as only 10% of the total Sb was present as Sb(III). In contrast to Sb, Pb, Cu and Zn soil solution concentrations remained unaffected by waterlogging, and shoot concentrations were significantly higher in the drained treatment for many plant species. Although showing an increasing trend over the season, shoot metal concentrations generally remained below regulatory values for fodder plants (40 μg g −1  Pb, 150 μg g −1 Zn, 15–35 μg g −1 Cu), indicating a low risk of contaminant transfer into the food chain under both oxic and anoxic conditions for the type of shooting range soil investigated in this study. Graphical abstract: Image 1 Highlights: Shooting range soil was subjected to waterlogged conditions in the field. Sb concentrations dropped with waterlogging; metal concentrations did not change. Sb concentrations in plants were not affected by waterlogging. Pb, Cu and Zn concentrations were lower or similar in plants on waterlogged soil. Pb, Cu and Zn concentrations remained below regulation values for forage plants. Abstract : Sb, Pb, Cu and Zn concentrations in plants growing on shooting range soil did not increase under waterlogging and generally remained below regulatory values for fodder plants.